Metacognition Analysis of Male Junior High School Students in Problem Solving Oriented to the Ethnomathematics of East Java Joglo Houses - Diana, Nanang; Faqihati, Deva Ananda Tuhfatul; Maftuh, Moh. Syukron (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2025)
The purpose of this study was to describe the metacognition of male junior high school students in problem solving oriented to the ethnomathematics of East Java joglo houses so that this research is a qualitative descriptive study, while the subject of this research is 1 male subject of SMP Negeri 2 Paciran. The data collection technique in this study uses test and interview techniques, where the test used is a problem solving test oriented to East Java joglo house ethnomathematics, then the test results and interviews are analyzed based on indicators of metacognition in problem solving. The validity of the data in this study uses time triangulation where the results of the first test and interview are compared with the results of the second test and interview until valid and reliable data are obtained with different time periods. While the data analysis method in this study consists of data reduction, presenting data, and drawing conclusions. The results of this study indicate that the metacognition of male junior high school students in solving problems oriented to East Java Joglo House Ethnomathematics at the stage of understanding the problem, and implementing a problem solving plan fulfills all indicators of metacognition, namely planning, monitoring and evaluation. However, at the stage of planning problem solving, male junior high school students do not fulfill the planning indicator because students do not plan the time used to solve the problem as well as at the stage of re-examining the solution obtained by male junior high school students do not fulfill the planning and monitoring indicators because they do not plan and monitor the problems given with different strategies or methods.